RANCANG BANGUN MEDIA PEMBELAJARAN KELISTRIKAN ELECTRONIC FUEL INJECTION (EFI) PADA MOTOR BENSIN - Amir, Amir (Universitas Muhammadiyah Tangerang, 2018)
Sains evolution and technology to carry positive effect to humams life. The fastes advance to positive consequence for education, in learn certainly must balanced with autompotive. So that don’t happened asymmetrical between education and automotive industry. This media comparability is basic theory and work method from electrical system with EFI (electronic fuel injetion) technology at fuel system and VTEC (Variable Valve Timing and lift electronic) at valve’s system and ECU (electronic control unit) at electrical system. To project arise electrical system at gasoline engine Honda VTEC as learms media whom efectif, so that students easy to studies work’s system, as either or media for escale proficiences. In to escalateresult of student, so that mature graduate whom skilled proficiencies.